Digital technologies and intra-African trade - (:unkn) unknown (My University, 2023)
Digitalisation has significantly increased in recent years in Africa and is considered a driver of economic growth and innovation. This is a great opportunity for African trade, which suffers greatly from a lack of trade infrastructure. By using a gravity model with data on 48 Sub-Saharan African (SSA) countries between 2000 and 2018, our study aims to show the effects of digital technology use on intra-African trade. The results suggest that Information and Communications Technology (ICT) use, particularly internet use, has positive and significant effects on exports and negative effects on imports of primary products and total goods. Intra-African exports of manufactured goods do not benefit from ICTs. Moreover, fixed-line telephone subscription has negative effects on intra-African exports. In addition, we find that the introduction of mobile payment services in SSA stimulates the export of products. Interestingly, we see that the negative effects of ICT use on exports become positive with access to electricity. Therefore, in line with the African free trade agreement (AfCFTA), it is essential for policy-makers to accelerate the digital transformation of economies, such as the digitalisation of information and customs procedures. It would also be beneficial to accelerate the deployment of fibre optics and improve access to electricity to connect populations and cities and African countries, which would reduce the trade costs in the continent.
Keywords: African Research